Drivers of lean 4.0 and their impact on manufacturing performance: A PLS-SEM study in the Malaysian automotive sector - Lim, Dara Affydah Mohd Affendi; Abidin, Nazim Hanis Zainal; Aripin, Norhana Mohd; Junaidi, Afdhal; Sazali, Norazlianie (Edelweiss Applied Science and Technology, 2026)
This study aims to identify the key factors for implementing Lean 4.0 in the automotive manufacturing industry and to examine its impact on the performance of the automotive industry in Malaysia. A quantitative research design employing a cross-sectional approach was adopted for this study. Simple random sampling was utilized. Data were collected from 93 automotive manufacturing firms in Malaysia, with respondents comprising individuals from middle and senior management. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to investigate the relationship between the constructs. The main findings reveal that human, supplier, and customer factors positively influence Lean 4.0 implementation, while process factors do not have a significant effect. This research offers insight into the factors influencing Lean 4.0 implementation in automotive manufacturing. Moreover, this study assists policymakers and SMEs in planning training initiatives, facilitating knowledge transfer, and enhancing innovation and continuous improvement. This study addresses a critical gap in the empirical validation of Lean 4.0 implementation within the Malaysian automotive manufacturing context.